Interpreting user-generated content: What makes a blog believeable? - Ahmad, Rahayu; Lutters, Wayne G. (Springer Berlin Heidelberg, 2011)
Blogs have democratized participation for everyone who wants to publish on the Internet.This trend, however, is problematic for readers trying to determine trustworthy and believeable sources.This blog diary study, allowed us to understand what aspects influenced believability and ultimately utililty through capturing routine blog-surfing behaviors.We found that literary appeal constituted by authentic and personalized stories positively influence the believability of blogs.Blogs that stimulated readers’ desire for novel and rare information also enhance their believability.Other factors that significantly correlated with believability included aesthetics, matching information needs and user expectations.